2021
DOI: 10.1177/08982643211046466
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Subjective Cognitive Impairment by Sexual Orientation and Gender in a National Population Based Study of U.S. Adults, 2013–2018

Abstract: Objectives: This is the first national population-based study to examine cognitive impairment disparities among sexual minority mid-life and older adults. Methods: Using the National Health Interview Survey (2013–2018), we compared weighted prevalence of subjective cognitive impairment by sexual orientation and gender, among those aged 45 plus, applying logistic regressions adjusting for age, income, education, race/ethnicity, and survey years. Results: Sexual minorities (24.5%) were more likely to have subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Cognitive function and memory loss were significant predictors of stress, even when controlling for other background characteristics and risk and protective factors. Existing literature demonstrates that sexual minorities experience significant disparities in subjective cognitive impairment compared to heterosexuals of similar age (Fredriksen-Goldsen et al, 2021). Caregivers’ difficulty tending to their own health needs is likely especially difficult for those that are experiencing their own challenges with memory loss and cognitive function (Buyck et al, 2011; Jones et al, 2011; NAC, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive function and memory loss were significant predictors of stress, even when controlling for other background characteristics and risk and protective factors. Existing literature demonstrates that sexual minorities experience significant disparities in subjective cognitive impairment compared to heterosexuals of similar age (Fredriksen-Goldsen et al, 2021). Caregivers’ difficulty tending to their own health needs is likely especially difficult for those that are experiencing their own challenges with memory loss and cognitive function (Buyck et al, 2011; Jones et al, 2011; NAC, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that SGM older adults are at elevated risks of cognitive impairment (Fredriksen-Goldsen et al, 2021). Deterioration of physical functioning and HRQOL with the progression of cognitive impairment is of major concern particularly in this historically and socially marginalized population given the disparities in limited activities and poor physical and mental health among SGM older adults compared to their heterosexual and cisgender counterparts (Fredriksen-Goldsen et al, 2022; Fredriksen-Goldsen, Kim, Shui et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to population-based studies, lesbian, gay, and bisexual older adults are at heightened risks of substance use, cardiovascular disease, HIV/AIDS, and mental distress (Fredriksen-Goldsen, Kim, Shui et al, 2017), which are known to be predictors of cognitive impairment in later life (Cooper et al, 2015). A recent study found that the prevalence of subjective cognitive impairment for lesbian, gay, and bisexual adults aged 45 and older was greater than that for their heterosexual counterparts (Fredriksen-Goldsen et al, 2021). Population-based disparities associated with increased risks for cognitive impairment were also found among transgender people as compared with cisgender people including the number of chronic conditions, disability, and poor mental health (Fredriksen-Goldsen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The sample demographics by sexual orientation were reported in a previous study (See Fredriksen-Goldsen et al, 2021); sexual minority adults were significantly younger (58 vs. 62) and had higher education (81% vs. 72% with some college or more education) than heterosexual counterparts. No significant differences were found in terms of race/ ethnicity or the rates of living at or below 200% of the federal poverty guidelines.…”
Section: Samplementioning
confidence: 98%
“…Psychological distress has been found to have a strong relationship with cognitive impairment (Hendrie et al, 2006), dementia, and Alzheimer’s disease (Wilson & Bennett, 2017). In a recent national study, sexual minority (those not heterosexual or straight) older adults had higher levels of subjective cognitive impairment (SCI), defined as “self-reported confusion or memory loss that is getting worse” (Alzheimer’s Association & CDC, 2018; CDC, 2019), compared to heterosexuals of similar age (Fredriksen-Goldsen et al, 2021). Another study using data across multiple states also documented higher levels of SCI (Flatt et al, 2018) compared to heterosexuals of similar age.…”
Section: Introductionmentioning
confidence: 99%